2010
DOI: 10.5005/jp-journals-10015-1036
|View full text |Cite
|
Sign up to set email alerts
|

Rectifying the Tooth Preparation Errors in All-Ceramic Restorations

Abstract: All-ceramic restorations have been used for long as restorative material in dentistry. However, the recent advances in both the material and technology of all-ceramic have made them a more viable treatment option. Several practitioners hesitate in giving this option to patient for fear of failure. This article describes all the failures of all-ceramic material and how to prevent them. In particular, the article highlights various errors that clinicians make while preparing tooth to receive all-ceramic restorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[13] Previous studies have shown that clinicians make the deviations from the recommended preparation methodology. [14] In our opinion, the easiest way to influence the quality of treatment with non-removable orthopedic structures is the optimization of tooth preparation. We developed a modified algorithm of tooth preparation for crowns, based on laboratory data.…”
mentioning
confidence: 99%
“…[13] Previous studies have shown that clinicians make the deviations from the recommended preparation methodology. [14] In our opinion, the easiest way to influence the quality of treatment with non-removable orthopedic structures is the optimization of tooth preparation. We developed a modified algorithm of tooth preparation for crowns, based on laboratory data.…”
mentioning
confidence: 99%